2001
DOI: 10.1080/003655101753218283
|View full text |Cite
|
Sign up to set email alerts
|

Early identification of bacteremia by biochemical markers of systemic inflammation

Abstract: Group II phospholipase A2 (PLA2-II), procalcitonin (PCT) and C-reactive protein (CRP) are useful indicators of the severity of inflammation in various infections. To compare their discriminatory abilities at an early phase of bacteremia, PLA2-II, PCT and CRP were measured upon admission and 24-48 h thereafter in 29 patients with bacteremia, non-bacteremic bacterial or viral infections. The levels of PLA2-II and PCT were higher in bacteremia than in non-bacteremic bacterial or viral infections. PCT was highest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
2

Year Published

2008
2008
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 25 publications
1
24
0
2
Order By: Relevance
“…All the studies conducted were prospective cross-sectional studies involving only human subjects. Only one study was published before the year 2000[26], whereas, the other three studies were published between the year 2001 to 2016[27, 29, 30]. All the four studies had a sample size of less than 100, ranging from 29 to 80 participants.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…All the studies conducted were prospective cross-sectional studies involving only human subjects. Only one study was published before the year 2000[26], whereas, the other three studies were published between the year 2001 to 2016[27, 29, 30]. All the four studies had a sample size of less than 100, ranging from 29 to 80 participants.…”
Section: Resultsmentioning
confidence: 99%
“…The release of sPLA2-IIA in these conditions is induced by inflammatory cytokines such as interleukin IL-6, IL-1β and tumor necrosis factor (TNF-α), which are key factors in the process of neutrophil adhesion and migration [2325]. Whilst the exact role of sPLA2-IIA in sepsis is still debatable, several small clinical trials have already shown that plasma levels of sPLA2-IIA exhibited positive correlation with subsequent diagnosis of bacteremia [26, 27]. Hence, in this systematic review, we aim to investigate the role of sPLA2-IIA as a biomarker for the detection of sepsis and bacterial infection in adults.…”
Section: Introductionmentioning
confidence: 99%
“…sPLA 2 was proposed as a sensitive marker of sepsis in adults as sPLA 2 reflects earlier biological events than CRP and the concentration declines earlier. 12,27 In this study, the diagnostic performance of sPLA 2 for suspected infection and sepsis was less than that of CRP, and better than I/T ratio. In clinical practice, newborn infants with clinical signs of infection receive antibiotics even when laboratory investigations are not suggestive of bacterial infection.…”
Section: Discussionmentioning
confidence: 58%
“…8,10,11 In adults, sPLA 2 is proposed as a sensitive marker for sepsis, and increased plasma levels of sPLA 2 are associated with development of multiple organ failure, vascular dilatation during shock and death. 6,7,12 The role of sPLA 2 in neonatal sepsis is unknown and its levels and relationship with well-recognized markers of inflammation have not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…C-reactive protein (CRP) has been used for predicting sepsis patient (21,22). In this years several markers have developed as sepsis markers such as LBP and procalcitonin (23,24).…”
Section: Discussionmentioning
confidence: 99%